Managers and their role in a modern sales organisation (Politics & Security, 2023)
This article provides a comparative analysis of four relevant sources focusing on the role of a manager in a modern sales organisation. Specifically, the analysis concerns publications entitled Marketing management (Kotler, P. & Keller, K. L., 2012), Marketing management: A contemporary perspective (Homburg, Ch., Kuester, S. & Krohmer, H., 2012), Marketing: an introduction (Armstrong, G. & Kotler, P., 2022) a Marketing: Real People, Real Choices (Solomon, M. R., Stuart, E. W. & Marshall, G. W., 2021).The comparative analysis examines in detail different approaches of the authors in the field of marketing management and retailing, focusing on five selected aspects of manager’s role which may be considered as the key to effective team management and the success of the modern sales organisation. In particular, these aspects include strategic planning and decision making; leadership and team management; employee development and motivation; implementation of new technologies and innovations; as well as sales team performance measurement and KPI tracking.The above resources offer different insights into selected aspects of manager’s role in the sales organisation. Detailed analysis provides a broader perspective and deeper understanding of how managers address key challenges, maximise their team’s performance, and achieve business goals. The result of this analysis is a comparison of different approaches and methods used in practice and their evaluation.
Keywords: sale; marketing; management; KPI